2020
DOI: 10.1029/2019jd031164
|View full text |Cite
|
Sign up to set email alerts
|

Retrievals of Convective Detrainment Heights Using Ground‐Based Radar Observations

Abstract: To better constrain model simulations, more observations of convective detrainment heights are needed. For the first time, ground‐based S band radar observations are utilized to create a comprehensive view of irreversible convective transport over a 7‐year period for the months of May and July across the United States. The radar observations are coupled with a volumetric radar echo classification scheme and a methodology that uses the convective anvil as proxy for convective detrainment to determine the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…In Figure 3b, a tropopause‐relative temperature analysis results in a local temperature minimum consistent with the tropopause altitude that is aligned between convective and echo‐free populations, with a lower tropopause temperature in convectively influenced air. This tropopause temperature difference is expected given previous findings of convective lifting and cooling of the tropopause in extratropical environments (Homeyer et al., 2014; Maddox & Mullendore, 2018; Starzec et al., 2020).…”
Section: Methodssupporting
confidence: 69%
See 1 more Smart Citation
“…In Figure 3b, a tropopause‐relative temperature analysis results in a local temperature minimum consistent with the tropopause altitude that is aligned between convective and echo‐free populations, with a lower tropopause temperature in convectively influenced air. This tropopause temperature difference is expected given previous findings of convective lifting and cooling of the tropopause in extratropical environments (Homeyer et al., 2014; Maddox & Mullendore, 2018; Starzec et al., 2020).…”
Section: Methodssupporting
confidence: 69%
“…Starzec et al. (2020) found that the LMD occurs between 4 and 5 km below the tropopause in the southern United States in May and July. Our study is based on the full warm season and is not fixed in geographic location, which could explain why this CO peak is observed higher in the UT.…”
Section: Resultsmentioning
confidence: 99%
“…Irreversible exchange can occur through gravity wave breaking in and near the overshooting top (as previously mentioned to be critical for AACP formation), Kelvin‐Helmholtz instabilities near cloud top, and tropopause‐level shallow continuity circulations coupled with differential advection (O’Neill et al., 2021; Pan et al., 2014; Phoenix et al., 2020). Additionally, the amount of overshooting convection and cross‐tropopause transport in simulations exhibits several sensitivities to storm characteristics (e.g., mode—discrete supercell versus mesoscale convective system or MCS) and to the characteristics of the lower stratospheric environment (Bigelbach et al., 2014; Homeyer et al., 2014a; Mullendore et al., 2005; Starzec et al., 2020). An isolated supercell tends to have a larger updraft and deeper overshooting compared to alternative storms, while an MCS has a large number of weaker overshoots that can achieve greater overall transport and STE (Bigelbach et al., 2014).…”
Section: Introductionmentioning
confidence: 99%